Capillaries for water management in polymer electrolyte membrane fuel cells. (29th November 2018) - Cho, J.I.S.; Neville, T.P.; Trogadas, P.; Bailey, J.; Shearing, P.; Brett, D.J.L.; Coppens, M.-O.
Abstract: Some of the new liquid water management systems in polymer electrolyte membrane (PEM) fuel cells hold great potential in providing flood-free performance and internal humidification. However, current water management systems entail major setbacks, which either inhibit implementation into state-of-the-art architectures, such as stamped metal flow-fields, or restrict their application to certain channel configurations. Here, a novel water management strategy is presented that uses capillary arrays to control liquid water in PEMFCs. These capillaries are laser-drilled into the land of the flow-fields and allow direct removal (wicking) or supply of water (evaporation), depending on the local demand across the electrode. For a 6.25 cm 2 active area parallel flow-field, a ∼92% improvement in maximum power density from capillary integration was demonstrated. The proposed mechanism serves as a simple and effective means of achieving robust and reliable fuel cell operation, without incurring additional parasitic losses due to the high pressure drop associated with conventional serpentine flow-fields. Highlights: New capillary-based water management strategy is presented for PEM fuel cells. The capillaries allow redistribution of liquid water across the electrode. Parallel flow-field modified with capillaries outperforms serpentine flow-field.